Environmental assessment of ozone layer depletion due to the manufacture of plastic bags - Jonathan-David Morales-Méndez; Ramón Silva-Rodríguez (Heliyon, 2018)
The results of a quantitative study about the potential environmental impact of ozone layer depletion due to the manufacture of plastic bags in a plant located in northern Colombia are presented in this article. The identification of the emitted gases is essential to determine their contribution to the depletion of the ozone layer and is measured in Kg. Eq. CFC-11 with LCA software, SimaPro. The criterion used in this evaluation are based on a life cycle analysis methodology and the objectives, scope and limitations of the productive system were defined based on this. From this information an inventory was made, taking as the main element the quantitative measurement of matter and energy flows for all inputs and outputs of the production process. The information about the process enabled the identification, characterization and assessment of the environmental impact of global warming related to the production of plastic bags, leading to the conclusion that the most polluting process is that of extrusion followed by the printing of plastic bags.